Influence of Climatic Parameters on the Photovoltaic Conversion Efficiency of a Polycrystalline Solar Panel - N.K. Tanasheva; A.A. Potapova; L.L. Minkov; A.S. Tussypbayeva; A.N. Dyusembaeva; E.K. Mussenova; B.B. Kutum; A.Z. Tleubergenova (Қарағанды университетінің хабаршысы. Физика сериясы)
The efficiency of electricity generation by solar panels depends on many factors, one of which is the temperature of the semiconductor layer. An increase in this parameter leads to a decrease in the efficiency of the module, since the speed of electron movement increases, therefore, the resistance increases. Conversely, the lower the temperature of the silicon cells, the lower the resistance and the higher the efficiency. However, the temperature of the silicon cells depends on a number of parameters: wind speeds, insolation, and ambient temperatures. Therefore, depending on the region and time of year, the same solar module will have different performance. Based on this, an urgent issue when planning the use of solar panels is the possibility of determining how much the efficiency of photovoltaic conversion in a particular area will decrease. Therefore, to study the variability of efficiency indicators, a simulation of the temperature change of the semiconductor layer of the polycrystalline solar panel KZPV 220 M60 was carried out, taking into account climatic parameters in winter and summer days for three cities of Kazakhstan — Petropavlovsk, Karaganda and Shymkent. As a result of modeling, it was found that on July 12, solar cells reach their maximum temperature of 64.4 °C in Shymkent, 49.8 °C in Karaganda and 52.1 °C in Petropavlovsk, while efficiency decreases by 2.7 %, 1.7 % and 1.8 %, respectively, relative to the efficiency of the solar module under standard conditions (insolation 1000 W/m2, temperature 25 °C, spectrum AM = 1.5). At the same time, on December 12, Tmax: in Shymkent 11.5 °C, in Karaganda — 15.8 °C, in Petropavlovsk — 16.7 °C, and efficiency increases by 0.9 %, 2.7 %, 2.8 %, respectively.